Stage Left: Canadian Theatre in the Thirties. A Memoir - Goldie, Terry (Labour / Le Travail, 1984)
This article reviews the book, "Stage Left: Canadian Theatre in the Thirties. A Memoir," by Toby Gordon Ryan.